Publicaciones sobre cine y medios de comunicación en Irlanda – 2019 - Ciara Chambers (Estudios Irlandeses, 2020)
This has been a big year for important books on Irish film with the publication of Ruth Barton’s Irish Cinema in the Twenty-First Century (Manchester University Press), Seán Crosson’s Gaelic Games on Film (Cork University Press) and the revised second edition of the Historical Dictionary of Irish Cinema (Roddy Flynn and Tony Tracy, Rowman & Littlefield). The ubiquity of Saoirse Ronan is evidenced in the covers of two of these volumes, both featuring her performance in Brooklyn (John Crowley, 2015) with a reminder that Irish film occupies a significant space in the contemporary international cinematic arena.